2021
DOI: 10.1002/eco.2341
|View full text |Cite
|
Sign up to set email alerts
|

The anatomy of two species of emergent macrophytes of the genus Polygonum differentially changes in response to water‐level fluctuations

Abstract: Temporal fluctuations in water levels are important ecological driving forces in shallow aquatic ecosystems. Alterations to fluviometric levels are even more conspicuous after the construction of dams, and aquatic macrophytes respond with anatomical and morphological adaptations to such changes. We performed an experiment to analyse the anatomical responses of two common Neotropical species of emergent macrophytes (Polygonum ferrugineum and P. acuminatum) to water-level fluctuations.The experiment simulated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
0
0
Order By: Relevance
“…Salinity is considered one of the main factors influencing the distribution and development of aquatic vegetation throughout these ecosystems (Nunes & Camargo, 2016). As mentioned, some species shows adaptations to survive to these different environmental conditions and can exhibit phenotypic plasticity to adapt to these new conditions (dos Santos Machado et al, 2021;Silveira et al, 2016). Studies have demonstrated that the relative amount of intercellular spaces in salinized plants may decrease noticeably, mainly due to the disruption to the arrangement of these tissues (de Villiers et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Salinity is considered one of the main factors influencing the distribution and development of aquatic vegetation throughout these ecosystems (Nunes & Camargo, 2016). As mentioned, some species shows adaptations to survive to these different environmental conditions and can exhibit phenotypic plasticity to adapt to these new conditions (dos Santos Machado et al, 2021;Silveira et al, 2016). Studies have demonstrated that the relative amount of intercellular spaces in salinized plants may decrease noticeably, mainly due to the disruption to the arrangement of these tissues (de Villiers et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Invasion success is often attributed to species with greater tolerances to various environmental conditions (e.g., temperature, nutrients and salinization of water bodies) (Clavero & García‐Berthou, 2005), as well as the adaptive strategies that these species can employ in their new environments to survive (Hayat et al., 2020), for example, rapid growth rate, dispersion (Xie et al., 2010) and adaptation of internal structures (e.g., increase in intercellular spaces; Silveira et al., 2016; dos Santos Machado et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…philoxeroides is a perennial species with stolons and rhizomes, featuring floating stems due to stem aerenchyma, thriving in aquatic margins, flooded areas, and dry land, reproducing vegetatively (Griseb, 2016) as well as P. ferrugineum that creates floating branches when flooded (de Assis Murillo et al, 2019;dos Santos Machado et al, 2021), whereas L. leptocarpa inhabiting riverbanks, lakes, and flooded areas (De Sousa et al, 2019).…”
Section: Introductionmentioning
confidence: 99%